Priority use of medium-chain fatty acids during high-intensity exercise in cross-country skiers - Lyudinina, A. Y.; Ivankova, G. E.; Bojko, E. R. (Journal of the International Society of Sports Nutrition, 2018)
Background: One of the topics discussed in sports science is the use of medium-chain saturated fat as an energy-saving nutrient additive when approaching high-intensity exercise. The purpose of this study was to compare the blood concentrations of medium-chain and long-chain fatty acids (FAs) across different intensity loads. Methods: Fifteen male highly trained athletes from the Russian cross-country skiing team participated in the study. Blood samples were drawn at rest, at the peak of veloergometric test with a growing exercise load till exhaustion (97-100% VO2max), and after competitions. The plasma FA profile was determined using gas-liquid chromatography. Results: We observed a substantial increase in the concentrations of capric acid ( 10:0) (+ 164.1%), lauric acid ( 12:0) (+ 223.9%), and myristic acid ( 14:0) (+ 130.2%) in skiers after a sprint distance (1.3 km). A less intense increase in the concentrations of these acids (p < 0.05) was observed after a middle length distance or cycle exercise «until exhaustion». No significant differences in long-chain saturated FA content relative to baselines during exercise tests or competitions were revealed. Conclusions: In conclusion, the obtained results demonstrate activation of the lipolysis and the oxidation of medium-chain FA involved in the energy supply for highly trained athletes at maximum exercise loads.